Defect formation in chemically reduced congruent LiTaO3: ab initio simulations and inelastic neutron scattering. Issue 38 (10th September 2021) - Köhler, Thomas; Zschornak, Matthias; Zbiri, Mohamed; Hanzig, Juliane; Röder, Christian; Funke, Claudia; Stöcker, Hartmut; Mehner, Erik; Meyer, Dirk C.
Abstract : Phonon spectra are measured to identify the point defect formation in LiTaO3 and separate it from further contributions of the structural phase transition as well as the ferroelectric domain structure. Abstract : Lithium tantalate (LiTaO3 ) has large technological importance due to numerous applications, especially for motion sensors, radiation detectors, and optical waveguides. In some manufacturing processes temperature treatments are applied to obtain the desired structure or composition. However, the temperature treatment influences the optical and electrical properties of the material due to the incorporation of defects. Unfortunately, the exact nature and concentration of these defects are only insufficiently known. In the present study, temperature-induced defect incorporation in congruent LiTaO3 crystals under vacuum at 1224 K is investigated. Inelastic neutron spectra are measured in situ to identify the point defects and separate them from further contributions of structural phase transition as well as ferroelectric domain structure. Inelastic neutron scattering data are analysed with respect to small defect concentrations by comparing with density functional theory results. The influence of ferroelectric domains is analysed by Raman and FT-IR spectroscopy. Combining the results of the different techniques, we will elucidate the role of and vacancies during the annealing of congruent LiTaO3 .